Dangerous curves : action heroines, gender, fetishism, and popular culture - Brown, Jeffrey A., 1966- (University Press of Mississippi, 2011)
Dangerous Curves: Action Heroines, Gender, Fetishism, and Popular Culture addresses the conflicted meanings associated with the figure of the action heroine as she has evolved in various media forms since the late 1980s. Jeffrey A. Brown discusses this immensely popular character type as an example of, and challenge to, existing theories about gender as a performance identity. Her assumption of heroic masculine traits combined with her sexualized physical depiction demonstrates the ambiguous nature of traditional gender expectations and indicates a growing awareness of more aggressive and violent roles for women.